THE EFFECTIVENESS OF TASK-BASED LANGUAGE TEACHING (TBLT) IN DEVELOPING SPEAKING SKILLS OF ECONOMIC FIELD STUDENTS - Zilola Mahmudova (Bright Mind Publishing, 2025)
This article examines how well students in the economics sector may improve their speaking abilities through Task-Based Language Teaching (TBLT). A learner-centered method called TBLT places a strong emphasis on using meaningful tasks to encourage language acquisition. The article focuses on economics students who need to communicate professionally in English for presentations, discussions, and commercial negotiations. A combination of student interviews, classroom observations, and pre- and post-tests was used in a mixed-methods approach. The findings show that TBLT greatly enhances students’ speaking abilities, especially their confidence, accuracy, and fluency. The study advises integrating TBLT into ESP (English for Specific Purposes) curriculum and concludes that it is an effective tool for teaching English to economics students.
Keywords: TBLT, task-oriented environments, ESP, speaking skills, fluency, accuracy, economic, assessment.